2019
DOI: 10.2147/cia.s218367
|View full text |Cite
|
Sign up to set email alerts
|

<p>Receptiveness Of GPs In The South Of Saxony-Anhalt, Germany To Obtaining Training On Technical Assistance Systems For Caregiving: A Cross-Sectional Study</p>

Abstract: BackgroundChallenges to general practitioners (GPs) as family doctors in Germany are growing because of the demographic situation. Technical assistance systems can improve the care for patients provided by GPs and care personnel to preserve autonomy. GPs are key persons in the health care team to recommend and facilitate access to technical solutions to influence their implementation into their patients’ homes.AimExplore the general receptiveness of GPs in Germany regarding state-of-the-art and modern assistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Bezüglich der Aufge-schlossenheit zum Wissen über Technologien konnten keine vergleichenden Zahlen zu verwandten Stichproben gefunden werden. Innerhalb der eigenen Forschungsgruppe existiert jedoch eine ähnliche Befragung von Hausärzten (Buhtz et al 2019) (Roland Berger GmbH 2017). Die angesprochenen Kompetenzen müssen in die bestehenden Berufsbilder und -rollen integriert und neben der grundständigen Ausbildung und dem Studium, auch in Fort-und Weiterbildungen entsprechend dem jeweiligen Qualifizierungsniveau und Tätigkeitsfeld vermittelt werden (Hübner et al 2017).…”
Section: Diskussionunclassified
“…Bezüglich der Aufge-schlossenheit zum Wissen über Technologien konnten keine vergleichenden Zahlen zu verwandten Stichproben gefunden werden. Innerhalb der eigenen Forschungsgruppe existiert jedoch eine ähnliche Befragung von Hausärzten (Buhtz et al 2019) (Roland Berger GmbH 2017). Die angesprochenen Kompetenzen müssen in die bestehenden Berufsbilder und -rollen integriert und neben der grundständigen Ausbildung und dem Studium, auch in Fort-und Weiterbildungen entsprechend dem jeweiligen Qualifizierungsniveau und Tätigkeitsfeld vermittelt werden (Hübner et al 2017).…”
Section: Diskussionunclassified
“…More than 90% of included studies reported organizational adoption barriers 13 , 15 , 17 , 18 , 22 , 23 , 28 44 (23/24), with more than half reporting high workload 17 , 22 , 29 , 30 , 34 , 36 44 and a lack of time 13 , 15 , 17 , 18 , 23 , 28 , 29 , 31 34 , 36 , 40 , 42 (each 14/24; 58%) as predominant barriers. Another 88% of studies identified social adoption barriers 13 , 15 , 17 , 18 , 22 , 23 , 28 32 , 35 44 (21/24). Of these, physicians’ familiarity with digital health solutions 15 , 17 , 18 , 22 , 23 , 28 , 30 32 , 36 , 38 44 (17/24; 71%) was the most cited social barrier, followed by overall awareness 15 , 18 , 22 , 23 , 29 , 30 , 32 , 35 , 43 , 44 (10/24; 42%) and patient preferences 15 , 18 , 23 , 29 31 …”
Section: Resultsmentioning
confidence: 99%
“…Another 88% of studies identified social adoption barriers 13 , 15 , 17 , 18 , 22 , 23 , 28 32 , 35 44 (21/24). Of these, physicians’ familiarity with digital health solutions 15 , 17 , 18 , 22 , 23 , 28 , 30 32 , 36 , 38 44 (17/24; 71%) was the most cited social barrier, followed by overall awareness 15 , 18 , 22 , 23 , 29 , 30 , 32 , 35 , 43 , 44 (10/24; 42%) and patient preferences 15 , 18 , 23 , 29 31 , 35 , 38 , 40 , 42 (10/24; 42%).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing with existing literature, our research finds that the successful implementation of FDCS in other countries has the following commonalities: (1) the development of FDCS is based on community health institutions or platforms, such as Patient-centred Medical Home (PCMH) in USA, 39 40 the family doctor-and-nurse offices in Cuba 41 and family doctors' community private clinic in UK, Germany, Netherlands, French and Canada. [42][43][44][45][46] Although the service model and service content of FDCS is different from the above countries, their health institutions are all over the country, forming the backbone of primary healthcare. (2) Education and training of family doctors is an important prerequisite to ensure the implementation of FDCS.…”
Section: Facilitators Of Fdcs For Disabled Older Adults In Beijingmentioning
confidence: 99%